Poly(N-vinylpyrrolidone)-assisted crystal growth of zeolitic imidazolate framework (ZIF-67) and electrochemical properties of its derivatives for flexible supercapacitors - Jain, Manisha; Joshi, Bhavana; Poddar, Pankaj (Crystal Growth and Design, 2024)
A simple and explicit wet chemical method enables the room-temperature crystallization of the zeolitic imidazolate framework (ZIF-67) using cotton-cloth (CC) as a substrate; where time-dependent Avrami's kinetic studies demonstrated sluggish nucleation and fast crystal growth resulting in unprecedented morphologies-truncated cubes [synthesized without poly(N-vinylpyrrolidone); PVP], and rhombic dodecahedra (with PVP) with average sizes ranging from 500 nm to 1.41 mu m; wherein amphiphilic PVP plays a crucial function of structure directing agent by modulation of complex formation and deprotonation equilibria. To study the potential of pristine ZIF-67 (ZP0) and PVP-functionalized ZIF-67 (ZP50, ZP100, and ZP200) grown on the CC substrate for application as a flexible electrode in supercapacitors, ZP0, ZP50, ZP100, and ZP200 were annealed to form CZP0, CZP50, and CZP100, respectively. Areal capacitances of 181 and 214 mFcm(-2) were achieved at a current density of 1 mAcm(-2) and a potential window of 1.6 V for CZP0 and CZP100, respectively, and compared to the derivatives without PVP; CZP100 exhibited a superior energy density of 76.3 mu Whcm(-2) and a capacitance retention of 84.3% after 5000 cycles at a current density of 0.5 mAcm(-2).